2016
DOI: 10.1139/cjpp-2016-0062
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic in vitro antioxidant activity and observational clinical trial of F105, a phytochemical formulation includingCitrus bergamia, in subjects with moderate cardiometabolic risk factors

Abstract: Abstract:We examined the clinical safety and efficacy of F105 in 11 subjects with moderate dyslipidemia. F105 is a combination of bergamot fruit extract (Citrus bergamia, BFE) and 9 phytoextracts selected for their ability to improve the antioxidant and anti-inflammatory activity of BFE. In vitro F105 exhibited a synergistic inhibition of oxygen radical absorbing capacity, peroxynitrite formation, and myeloperoxidase activity. Following 12 weeks of F105 daily, no treatment-related adverse events or changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The study carried out by Cai et al (2017) did not find statistically significant differences. Even though, it is important to note that Babish et al (2016), Bruno, Pandolfo, Crucitti, Cacciola, et al (2017) and Dahlberg et al (2017) showed light although significant decreases in HDL cholesterol concentration, that ranged from 1% to 6.5%.…”
Section: Change On Lipid Profilementioning
confidence: 94%
See 1 more Smart Citation
“…The study carried out by Cai et al (2017) did not find statistically significant differences. Even though, it is important to note that Babish et al (2016), Bruno, Pandolfo, Crucitti, Cacciola, et al (2017) and Dahlberg et al (2017) showed light although significant decreases in HDL cholesterol concentration, that ranged from 1% to 6.5%.…”
Section: Change On Lipid Profilementioning
confidence: 94%
“…There was quite heterogeneity in clinical characteristics of populations. In summary, two trials recruited subjects with overweight or obesity and other cardiovascular risk factors (Dahlberg et al 2017) or metabolic syndrome (Di Folco et al 2018), four trials included subjects with mixed hyperlipidemia (Gliozzi et al 2013; Mollace et al 2011;Cai et al 2017;Babish et al 2016), one trial involved subjects with isolated hypercholesterolemia (Toth et al 2015), one trial recruited participants with previous ischemic heart disease (Campolongo et al 2016), two similar trials recruited subjects under second-generation antipsychotics (SGA) treatment (Bruno, Pandolfo, Crucitti, Cacciola, et al 2017;Bruno, Pandolfo, Crucitti, Maisano, et al 2017), and one trial included women with breast cancer and receiving aromatase inhibitors treatment (Izzo et al 2017). Five studies had a single-arm intervention, while six of them showed double or multiple-arm designs by comparing different doses of bergamot, using a placebo or statin group as comparison arm.…”
Section: Participants and Main Study Characteristicsmentioning
confidence: 99%
“…In 2016, (Babish et al (2016) showed that a 250 mg dose of bergamot fruit extract (BFE) and 110 mg of a blend of nine other phytoextracts showed a decrease in total cholesterol, LDL, and apolipoprotein B (p < 0.05). A post hoc analysis showed other significant effects only in eight subjects with HbA1c > 5.4 and HOMA-IR score >2 or elevated triglycerides: reduction in triglycerides and plasminogen activator inhibitor type 1 (PAI-1) (p < 0.05).…”
Section: Effects On Humansmentioning
confidence: 99%
“…Although native to South-East Asia, 80% of bergamot is produced in Calabria, southern Italy, where it grows extensively. The main preparations used are bergamot extracts (BE), with high content of flavonoids, such as neoeriocitrin, neohesperidin, naringin (Toth et al, 2015), bergamot polyphenolic fraction (BPF) (Bruno, Pandolfo, Crucitti, Maisano, Zoccali, et al, 2017), bergamot essential oil (BEO) (Watanabe et al, 2015), and aromasticks with bergamot/sandalwood or frankincense/mandarin/lavender (Dyer, Cleary, McNeill, Ragsdale-Lowe, & Osland, 2016) bergamot/vetivert/geranium (Wiebe, 1998), bergamot/lavender/cedarwood (Graham, Browne, Cox, & Graham, 2003) and bergamot juice (BJ) (Impellizzeri et al, 2015), bergamot/boxthorn extract (Shao, 2003) or bergamot essential oil plus other citrus essential oils plus grapefruit juice (Li, Zhu, Han, & Zhang, 2016) or bergamot flavonoids and other phytoextracts (Babish et al, 2016;Saiyudthong & Marsden, 2011). Bergamot essential oil (BEO) and bergamot juice (BJ) contain up to 93-96% of volatile compounds, such as monoterpenes (25-53% of limonene), as well as discrete quantities of linalool (2-20%) and linalyl acetate (15-40%).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is a potent risk factor for kidney disease, as obese subjects have a greater chance of developing diseases such as diabetes and hypertension [68]. Several studies have also shown that being overweight or obese may directly cause renal dysfunction and kidney damage through a direct role in the endocrine activity of adipose tissue [71][72][73][74]. Indeed, many adipokines that are produced by higher visceral adipose tissue have been involved in the development of insulin resistance, inflammation, and oxidative stress [65,68,75,76].…”
Section: Oxidative Stress and Chronic Kidney Diseasementioning
confidence: 99%